Lilium Mackliniae Sealy an Endemic Lily of North East India, its Distribution and Status in the Wild - Mao, A. A.; Gogoi, R. (Indian Forester, 2013)
The paper reports Lilium mackliniae, an endemic lily from north east India, its distribution and status in natural habitats. The main threats to the species and habitats due to frequent forest fire and rapid colonization by a dwarf bamboo after forest fire are discussed along with conservation measures which need to be taken for its protection.